Quality drivers for e-pharmaceuticals system management: a theoretical framework. (1st September 2004) - Cook, David P.; Joseph, Jimmie L.; Morton, Russell S.
Approximately 41 million US adults currently use the internet for healthcare, and approximately 4.6 million have used the internet to make an e-pharmaceuticals or health and beauty product category purchase. Increased data access, to the general public, has given rise to a class of sophisticated medical goods and services consumers. Exposure to e-commerce has supplanted the novelty of purchasing online with a desire for a quality purchasing experience comparable with, or superior to, offline healthcare encounters. With experienced and sophisticated consumers, quality is essential for e-marketplace success. This paper examines the components of service quality to provide a framework for guiding e-pharmacy development and evaluation.